2013
DOI: 10.5296/ijld.v3i3.3990
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence and Occupational Knowledge as Determinants of Career Choice Intentions among Undergraduate Students in Tanzania

Abstract: The purpose of this study was to examine the extent to which occupational knowledge and social influence from significant others predict intentions of undergraduate students to join their careers upon completion of their studies in Tanzania. Based on its quantitative character, a cross-sectional survey design was opted. A convenient sample of 100 first and finalist undergraduate students (63 males, 37 females; age range 19 to 40 years) participated in this study. The structured questionnaire was used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 10 publications
4
30
1
Order By: Relevance
“…Parallel with the previous studies a majority of the pre-service teachers plan to continue teaching English after graduation (Amani, 2013;Aksu et al, 2010). The results illustrated that 136 student teachers out of 213 consider teaching as a whole life career.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Parallel with the previous studies a majority of the pre-service teachers plan to continue teaching English after graduation (Amani, 2013;Aksu et al, 2010). The results illustrated that 136 student teachers out of 213 consider teaching as a whole life career.…”
Section: Discussionsupporting
confidence: 66%
“…The influence of the second and the third variables mentioned by Rots et al (2010) is confirmed in other studies as well (Bruinsma and Jansen, 2010;DeAngelis, Wall & Che, 2013). Amani (2013) reports that career intentions are affected by significant others, like family members, friends and lecturers, and their occupational knowledge. However, in Rots et al (2010) significant others are claimed to be ineffective on teacher career intentions.…”
Section: Introductionsupporting
confidence: 68%
“…(Eccles, 1997;Epstein, 1992;Haverman & Wolfe, 1995;Windham, 1996;Howe, 1997;Davies, Spencer & Steele, 2005;Walton & Cohen, 2007. Thus, occupational decisions taken by young people is therefore a combination of both personal (those originating within the individual) and situational factors (forces enabled from social context) (Amani, 2013). The personal factors are those that include cognitive and mental processes which dictate career decision making such as attitude, self-concept, self-efficacy and knowledge (Sharf, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The situational or environmental factors which include social or external factors from the society may influence ones career decisions. These social pressures which are valuable to the students may come from parents, relatives, teachers, friends, peers and the society in general which partly determines the decision of a person whether to join a career or not (Amani, 2013). In addition, the interdependency of family, school and community culture plays a critical role in shaping the youth's occupational choice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among such factors include family socio-economic backgrounds such as income and types of occupations (Zahari et al, 2005), parental influence, family, friends or significant other people of reference (Ajzen, 1991, Amani, 2013, income and future career prospects (Bhat et al, 2012), intentions, self-esteem and ease of employment (Ajzen, 2006, Amani, 2013. Orenuga and Costa (2006) also identified four major motives for the choice of specialisation as interest, prestige, good employment opportunities and regular work hours.…”
Section: Introductionmentioning
confidence: 99%